Antiplatelet activity of new derivatives of benzimidazole containing sterically hindered phenolic group in their structure - Alexander A. Spasov; Aida F. Kucheryavenko; Ksenia A. Gaidukova; Vadim A. Kosolapov; Olga N. Zhukovskaya (Research Results in Pharmacology, 2020)
Introduction: Cardiovascular diseases are currently the leading cause of global disability and mortality. According to the centers for disease control and prevention, the average life expectancy of a person would be 10 years longer but for a high prevalence of cardiovascular diseases, and if antiplatelet drugs and special therapy were used. Materials and methods: Antiplatelet activity of the novel benzimidazole derivatives containing a sterically hindered phenolic group in their structure has been investigated in vitro, using a model of ADP-induced platelet aggregation of rabbit’s plasma. The compounds exhibiting high antiplatelet activity and acetylsalicylic acid, as a reference drug, were examined for antioxidant properties in an ascorbate-dependent model of lipid peroxidation. Results: It was established that the compounds with high antiplatelet activity demonstrated the pronounced antioxidant action. The compound RU-1144 (1-(3,5-ditretbutyl-4-hydroxyphenyl) -1-hydroxypropyl)-phenyl-pyrimidobenzimidazole hydrochloride), in in vitro experiments, had a pronounced antiplatelet activity, surpassing the reference drug acetylsalicylic acid by 21.8 times; in the study of antioxidant activity, the leader compound was inferior to the reference drug dibunol by 1.7 times. By inhibiting intravascular platelet aggregation in vivo, this compound exceeded acetylsalicylic acid by 1.5 times and was slightly inferior to clopidogrel by 1.4 times. Discussion: Benzimidazole derivatives with a hindered phenolic substituent in their structure exhibited antiplatelet and antioxidant properties. It was established that the compounds with high antiplatelet activity demonstrated the pronounced antioxidant action. Conclusion: The chemical class of benzimidazole derivatives with a hindered phenolic substituent in their structure is promising for the search for new antiaggregant and antioxidant drugs.